Invasion genetics of American cherry fruit fly in Europe and signals of hybridization with the European cherry fruit fly. Issue 1 (6th February 2013) - Johannesen, Jes; Keyghobadi, Nusha; Schuler, Hannes; Stauffer, Christian; Vogt, Heidrun
Abstract The American cherry fruit fly is an invasive pest species in Europe, of serious concern in tart cherry production as well as for the potential to hybridize with the European cherry fruit fly, Rhagoletis cerasi L. (Diptera: Tephritidae), which might induce new pest dynamics. In the first European reports, the question arose whether only the eastern American cherry fruit fly, Rhagoletis cingulata (Loew) (Diptera: Tephritidae), is present, or also the closely related western American cherry fruit fly, Rhagoletis indifferens Curran. In this study, we investigate the species status of European populations by comparing these with populations of both American species from their native ranges, the invasion dynamics in German (first report in 1993) and Hungarian (first report in 2006) populations, and we test for signals of hybridization with the European cherry fruit fly. Although mtDNA sequence genealogy could not separate the two American species, cross‐species amplification of 14 microsatellite loci separated them with high probabilities (0.99–1.0) and provided evidence for R. cingulata in Europe. German and Hungarian R. cingulata populations differed significantly in microsatellite allele frequencies, mtDNA haplotype and wing pattern distributions, and both were genetically depauperate relative to North American populations. The diversity suggests independent founding events in Germany and Hungary. Within each country, R. cingulata displayed little or no structure in any trait, which agrees with rapid local range expansions. In cross‐species amplifications, signals of hybridization between R. cerasi and R. cingulata were found in 2% of R. cingulata individuals and in 3% of R. cerasi. All putative hybrids had R. cerasi mtDNA indicating that the original between‐species mating involved R. cerasi females and R. cingulata males.